2014
DOI: 10.4102/ajlm.v3i1.132
|View full text |Cite
|
Sign up to set email alerts
|

Phlebotomy and quality in the African laboratory

Abstract: Phlebotomy, the act of drawing blood through venepuncture, is one of the most common medical procedures in healthcare, as well as being a basis for diagnosis and treatment. A review of the available research has highlighted the dearth of information on the phlebotomy practice in Africa. Several studies elsewhere have shown that the pre-analytical phase (patient preparation, specimen collection and identification, transportation, preparation for analysis and storage) is the most error-prone process in laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…This practice may have accounted for the low SRR in this study. Some reports have concluded that the rates of pre-analytic errors are lower for outpatients, for whom phlebotomy procedures are performed by personnel under direct laboratory control [22] [23].…”
Section: Discussionmentioning
confidence: 99%
“…This practice may have accounted for the low SRR in this study. Some reports have concluded that the rates of pre-analytic errors are lower for outpatients, for whom phlebotomy procedures are performed by personnel under direct laboratory control [22] [23].…”
Section: Discussionmentioning
confidence: 99%
“…Blood sampling by venipuncture for various laboratory analyses is one of the most invasive common procedures, yet at the same time most underrated procedures in a hospital setting ( 1 , 2 ). Although venipuncture is considered as safe and foolproof procedure for patients, several studies show that it carries inherent risks ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the number of nominated person for transportation of infectious substances was very low (19.4%). Also, standard shipping boxes were not available for the majority of state laboratories [20][21].…”
Section: Discussionmentioning
confidence: 99%